Distostylus gen. nov., a monotypic therevine genus (Diptera: Asiloidea: Therevidae) from the Caribbean Island of Dominica - Metz, Mark A.; Webb, Donald W. (Zootaxa, 2003)
A new monotypic genus, Distostylus Webb (Diptera: Therevidae), based on a new species, irwini Webb, is described from specimens collected on the Caribbean island of Dominica. An hypothesis of the placement of the new taxon is generated based on a matrix of 30 morphological characters. This genus is associated with the Lindneria genus group and shows some affinities to the amber fossil species Ambradolon grimaldii Metz & Irwin.